ANALYSIS OF DETERMINANTS OF STUNTING AMONG CHILDREN AGED 24-59 MONTHS IN PAMENANG VILLAGE, PAGELARAN SUB-DISTRICT, PRINGSEWU DISTRICT - Abdullah, Abdullah; Dian Khairani, Masayu; Akhriani, Mayesti; Rica Pratiwi, Amali; Nurhayati, Aftulesi (Universitas Aisyah Pringsewu, 2025)
The problem of malnutrition in Indonesia is currently being aggressively carried out various prevention and control efforts by involving all sectors, namely the problem of stunting. The determinants of stunting are lack of nutritional intake, infectious diseases, food availability, parenting, environmental health and health services. In addition, demographic and educational factors contribute to stunting. The purpose of this study was to determine the relationship between the characteristics of parents and toddlers with stunting of toddlers aged 24-59 months. This study is an observational study with a quantitative approach and uses a cross sectional research design in Pamenang Village, Pagelaran District, Pringsewu Regency. The sample in this study were toddlers aged 24-59 months totaling 151 toddlers. The results of the study found stunting toddlers as much as 29.8%. The results of statistical analysis showed no significant relationship between age (p = 0.640) gender (p = 0.354), history of disease (p = 0.326), mother's education level (p = 0.090) and father's education level (p = 0.225) with stunting. Suggestions that can be given are that the prevention and handling of stunting is prioritized in toddlers aged 36-59 months.